2009
DOI: 10.1016/j.bmcl.2009.04.138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel inhibitor of JAK2 tyrosine kinase by structure-based virtual screening

Abstract: Janus kinase 2 (JAK2) plays a crucial role in the pathomechanism of myeloproliferative disorders and hematologic malignancies. A somatic mutation of JAK2 (Val617Phe) was previously shown to occur in 98% of patients with polycythemia vera and 50% of patients with essential thrombocythemia and primary myelofibrosis. Thus, effective JAK2 kinase inhibitors may be of significant therapeutic importance. Here, we applied a structure-based virtual screen to identify novel JAK2 inhibitors. One JAK2 inhibitor in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…Furthermore, the reduction in phospho-STAT5 correlates very well with G6-mediated reduction in HEL cell growth (Fig. 1) and inhibition of Jak2 kinase activity (19). As such, our data suggest that G6 inhibits HEL cell growth via a Jak2/STAT5-dependent mechanism.…”
Section: G6supporting
confidence: 52%
See 3 more Smart Citations
“…Furthermore, the reduction in phospho-STAT5 correlates very well with G6-mediated reduction in HEL cell growth (Fig. 1) and inhibition of Jak2 kinase activity (19). As such, our data suggest that G6 inhibits HEL cell growth via a Jak2/STAT5-dependent mechanism.…”
Section: G6supporting
confidence: 52%
“…G6 Inhibits Jak2-V617F-dependent Constitutive Activation of STAT5-We previously showed that G6-mediated reduction in HEL cell numbers directly correlates with suppression of Jak2 kinase activity (19). We now wanted to determine whether treatment with G6 and subsequent HEL cell growth inhibition also correlated with reduced STAT signaling.…”
Section: G6mentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, tyk2 with JAK1 and JAK2 is associated with type I interferon, P40, IL-12 and IL-23 (10). Hyperactive Janus kinase leads to an abnormal proliferation in a series of hematological malignancies such as myeloid and lymphoid leukemia, Hodgkin lymphoma and B-cell non-Hodgkin lymphomas (11). In 1985, the first study related to interaction of mutations in JAK kinases and hematological malignancies were performed.…”
Section: Signaling Of Jaks and Statsmentioning
confidence: 99%